Conversion of CH4 Catalyzed by Gas Phase Ions Containing Metals. Issue 33 (13th April 2022) - Yang, Yuan; Zhao, Yan‐Xia; He, Sheng‐Gui
Abstract: Methane is an abundant and cheap feedstock to produce valuable chemicals. The catalytic reaction of methane conversion generally requires the participation of multiple molecules (such as two or three CH4 molecules, O2, CO2, etc.). Such complex process includes the cleavage of original chemical bonds, formation of new chemical bonds, and desorption of products. The gas phase study provides a unique arena to gain molecular‐level insights into the detailed mechanisms of bond‐breaking and bond‐forming involved in complicated catalytic reactions. In this Review, we introduce the methane conversion catalyzed by gas phase ions containing metals and three topics will be discussed: (1) the direct coupling of methane molecules, (2) the conversion of CH4 with O2, O3 and N2 O, and (3) the conversion of CH4 with CO2 and H2 O. The obtained mechanistic aspects may provide new clues for rational design of better‐performing catalysts for conversion of methane to value‐added products. Abstract : This Review article discusses the significant progress that has been made for catalytic methane conversion in the gas phase, with focus on the coupling reactions of CH4 molecules and of CH4 with other substrates (O2, O3, N2 O, CO2, and H2 O) catalyzed by ions containing metals. The mechanistic details for generation of C−C coupling and C‐O coupling products from methane have been provided at a strictly molecular level.